2020
DOI: 10.1038/s41467-020-15046-w
|View full text |Cite
|
Sign up to set email alerts
|

Identification of novel breast cancer susceptibility loci in meta-analyses conducted among Asian and European descendants

Abstract: Known risk variants explain only a small proportion of breast cancer heritability, particularly in Asian women. To search for additional genetic susceptibility loci for breast cancer, here we perform a meta-analysis of data from genome-wide association studies (GWAS) conducted in Asians (24,206 cases and 24,775 controls) and European descendants (122,977 cases and 105,974 controls). We identified 31 potential novel loci with the lead variant showing an association with breast cancer risk at P < 5 × 10 −8. The … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 57 publications
(66 citation statements)
references
References 49 publications
1
65
0
Order By: Relevance
“…Family studies using linkage analysis have identified several rare mutations with strong effects (i.e., highly penetrant), notably at BRCA1, BRCA2, PALB2, ATM , and CHEK2 loci, conferring lifetime risk of breast cancer 31 . The large-scale genome-wide association studies (GWAS) have identified more than 200 susceptibility loci, each of which confers a small risk for breast cancer development 32 . However, the mechanism steering these genetic associations remains largely unknown because most variants are located in non-coding regions and are not in strong linkage disequilibrium with known protein‐coding variants 33 .…”
Section: Discussionmentioning
confidence: 99%
“…Family studies using linkage analysis have identified several rare mutations with strong effects (i.e., highly penetrant), notably at BRCA1, BRCA2, PALB2, ATM , and CHEK2 loci, conferring lifetime risk of breast cancer 31 . The large-scale genome-wide association studies (GWAS) have identified more than 200 susceptibility loci, each of which confers a small risk for breast cancer development 32 . However, the mechanism steering these genetic associations remains largely unknown because most variants are located in non-coding regions and are not in strong linkage disequilibrium with known protein‐coding variants 33 .…”
Section: Discussionmentioning
confidence: 99%
“…We identified seven associations for breast cancer (in addition to the eight reported above) that were new in the context of the breast cancer data set used in this study but have since been reported for breast cancer at P < x 10 -8 in the meta-analysis by Zhang et al 13 described above (five of the seven associations; Supplementary Table 5) or in a trans-ancestry genome-wide association meta-analysis by Shu et al 15 (two of the seven associations; Supplementary Table 5). Shu et al combined the breast cancer data set used in this study with a data set that included over 24,000 breast cancer cases and 24,000 controls of Asian ancestry.…”
Section: Cancer Susceptibility Loci Not Previously Identified For Onementioning
confidence: 83%
“…This result is consistent with emerging evidence that the cell of origin of HGSOCs, the most common and aggressive histotype of ovarian cancer, is in the fallopian tube 67,68 , and suggests that combining data from other cancers improves the ranking of genes associated with ovarian cancer risk that are also fallopian tube-specific. We identified nine lead SNP-breast cancer associations in our study that were new in the context of the breast cancer data set used here but have recently been identified in two larger breast cancer GWAS 13,15 . These breast and ovarian cancer findings, in particular, demonstrate that cross-cancer GWAS meta-analysis can be a powerful approach to the identification of new cancer susceptibility loci.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the last decade, GWAS conducted on many different tumor types, including pancreatic [22], ovarian [23], lung [24], prostate [25], and breast cancer [26], identified numerous risk alleles, most of which are common and individually confer only a modest increase in disease risk. For instance, GWAS revealed 31 novel genetic susceptibility loci associated with the genetic predisposition for breast cancer [27] and 12 novel loci for prostate cancer [28]. Notably, the vast majority of genetic variants identified through GWAS (>90%) are located in the non-coding regions of the genome [29].…”
Section: Introductionmentioning
confidence: 99%